PERSEPSI PEMUSTAKA TERHADAP KETERSEDIAAN KOLEKSI DI PERPUSTAKAAN PASCASARJANA UNIVERSITAS NEGERI PADANG - M. Rasyid; Gustina Erlianti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe; (1) student perceptions of collections seen from the relevance of collections in the Postgraduate Library of Padang State University; (2) student perceptions of collection availability seen from user-oriented aspects in the Postgraduate Library of Padang State University; (3) student perceptions of collection availability seen from the completeness of collections in the Postgraduate Library of Padang State University; (4) student perceptions of collection availability seen from the up-to-dateness of collections in the Postgraduate Library of Padang State University. Samples were taken from users who actually came to the research location, with a sample of 100 respondents. This type of research uses quantitative research with descriptive methods. Data in this study were collected using questionnaires or surveys. The results of the study indicate that the perception of library users towards the availability of collections at the Postgraduate Library of Padang State University is in the high category with an average score of 3.25. The awareness and usefulness indicators obtained a very high category, accessibility was also in the very high category, while relevance, adequacy, and satisfaction were in the high category. In general, the library collection is considered to have been able to meet the academic needs of library users, although the development and renewal of collections still need to be improved continuously.